International conflict management [ - Butler, Michael J. , 1972- (Routledge, 2009)
Presents an overview of the logic, evolution, application and outcomes of the 5 major approaches of international conflict management: traditional peacekeeping; peace enforcement and support operations; negotiation and bargaining; mediation; and, adjudication. This book provides an understanding of the strengths and weaknesses of these techniques.